Risk factors of recurrent cervical intraepithelial neoplasm 2/3 after primary excisional conization/LEEP treatments: A follow-up nationwide cohort study - Hung Shen; Mei-Hsuan Wu; Jian-Jhih Lin; Heng-Cheng Hsu; Yi-Jou Tai; Chia-Ying Wu; Chia-Yi Lee; Yen-Han Wang; Ying-Cheng Chiang (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Objective: Follow-up human papillomavirus (HPV) testing 6 months after treatment is suggested for women with cervical intraepithelial neoplasm (CIN) 2/3. However, the Pap smear remains the only feasible tool in areas with limited resources. Our study aimed to evaluate the risk factors of recurrent CIN2/3 after excision treatment by follow-up Pap smear in a nationwide database. Methods: We retrospectively identified women receiving excision treatment for CIN2/3 from 2007 to 2016 in the Taiwan National Cervical Cancer Screening Database. Risk factors of recurrence including age, education status, follow-up frequency, and the results of serial follow-up Pap smears were analyzed. Results: In total, 11595 women were enrolled, 287 having recurrent CIN2 + diseases (cumulative incidence of recurrence of 24.8/1000 people). The incidence of recurrent CIN2 + lesions was highest in the over 60-year-old age group (12.12/1000 person-years). For the first follow-up Pap smear, the highest recurrence rate was in the AGC/HSIL+ group (106.6/1000 people). Multivariate Cox regression analysis revealed that over 60 years of age, AGC/HSIL+ in the first follow-up pap smear, and any abnormal pap smear result within the first year after treatment were risk factors of CIN2/3 recurrence. Conclusions: In patients receiving excision for CIN2/3, the recurrence risk was higher in patients older than 60 years of age, and who had any abnormal follow-up Pap smear results, especially AGC/HSIL+ , in the first year after treatment.